The relationship between occupational health and safety and sustainability in the light of the sustainable development goals (SDGS): a bibliometric analysis from 2002 to 2022 - Maia, Macilene Maria Monteiro; Bastos, Marcos Filho Lima; Paiva, Antonia Claudenice Pinheiro de Almeida; Santos, Josicleyton Azevedo dos; Perlin, Ana Paula; Rocha, Miriam Karla (Brazilian Journal of Production Engineering, 2025)
The growing public interest in environmental, social and governance issues requires that all organizations address the UN Sustainable Development Goals (SDGs). The main objective of this research is to explore the relationship between occupational health and safety and sustainability, aligned with the SDGs. To this end, a bibliometric approach was adopted, analyzing 20 years (2002-2022) of academic production in the Web of Science (WoS) database. The justification is the need to understand how occupational safety practices connect to sustainability principles in the global context of the pursuit of sustainable development. The results revealed an exponential increase in academic production, highlighting works correlated to occupational health and safety and the sustainability of the following SDGs: 3 (Health and Well-being), 11 (Sustainable Cities and Communities) and 12 (Sustainable Consumption and Production). The predominant areas include Environmental Sciences and Public Occupational Health. Key journals include: Sustainability, International Journal of Environmental Research and Public Health, Safety Science and Journal of Cleaner Production. The study highlighted the need for integrated approaches that combine occupational safety and sustainability, aiming for safer workplaces aligned with the principles of the SDGs, contributing to human and environmental well-being.
Keywords: Health and safety at work; Sustainability; Bibliometric research; Sustainable Development Goals